KROMONGAN MUARA ENIM SUMATERA SELATAN: SEBUAH KAJIAN BENTUK, SISTEM PELARASAN DAN KOHESI SOSIAL - Tika Puspita Sari; Lutfia Okta Riwayati (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2025)
This research explores the kromongan in Muara Enim, South Sumatera, as a form of traditional art that has aesthetic, musical, and social value. The study focuses on three main aspects, namely presentation form, tuning system, and social cohesion. This study uses descriptive analysis methods. As a form of qualitative research, data is obtained from actual events, without any intervention from the researcher. Data processing was carried out using inductive analysis techniques, namely by interpreting the data based on patterns, themes, and categories that emeged during the research process. To support the collection of songs in kromongan games, namely Jarum Pelitas, Rejung tetambang, Siamang Jauh, and Saluang Mudik. These five forms can be seen from the structure of the peninting instrument. For the people of Muara Enim Rancap, Jarum pelitas, Rejung Tetambang, Siamang Jauh, and Saluang mudik are important entities in kromongan because these five things are manifestations of the art and culture of the Kromongan Muara Enim community, contributing to the creation of a solid and socially empowered society.